Overconfidence Bias and Financial Literacy on Generation Z Investment Decisions: The Moderating Role of Risk Perception - Metilda Dwi Putri Landang; Baldric Siregar; Miswanto Miswanto; Frasto Biyanto (CV. Ulil Albab Corp, 2026)
This study was conducted to examine the effect of overconfidence bias and financial literacy on Generation Z investment decisions, using risk perception as a moderating variable. This study employed a quantitative approach using a survey method through a structured questionnaire distributed to respondents. Sampling was carried out using purposive sampling involving 150 young Generation Z investors, born between 1997 and 2012, who were still actively investing in the Indonesian capital market. Data analysis was conducted using PLS-SEM with the assistance of SmartPLS 3.0. The results showed that overconfidence bias had no significant effect on Generation Z investment decisions (β = 0.082; p = 0.119), whereas financial literacy had a positive and significant effect on investment decisions (β = 0.324; p = 0.000). Risk perception was found to negatively moderate the effect of overconfidence bias on investment decisions (β = −0.169; p = 0.039), but it was not found to moderate the effect of financial literacy on investment decisions (β = −0.111; p = 0.088). This research model was able to explain 55.7% of the variance in Generation Z investment decisions (R² = 0.557). These findings confirm that financial literacy is the most dominant factor in improving the quality of investment decisions, while increasing risk awareness is needed as a control mechanism for the impact of overconfidence among young investors in the Indonesian capital market.